Hospital in-reach family-centred social prescribing pilot for children with neurodisability: mixed methods evaluation with social return on investment analysis - Laura Gordon; Megan Hastry; Angela Bate; Katie Gordon; Emily Greaves; Simoni Dimitriadou; Tim Rapley; Anna Purna Basu (BMC Health Services Research)
Abstract Background Social prescribing link workers support individuals to engage with community resources, co-creating achievable goals. Most schemes are community-based, targetting adults. Vulnerable populations including hospitalized children with neurodisability and their families, could also benefit from social prescribing. Aims To pilot a hospital-initiated social prescribing service for children with neurodisability and their families; to explore its feasibility, acceptability and undertake social return on investment (SROI) analysis. Methods Mixed-methods cohort study with SROI analysis. We recruited children aged < 16y with neurodisability, identified during inpatient stays, their parents/carers and siblings. Participants received link worker support for 6 months, extending beyond hospital discharge. Pre- and post-intervention pilot data covered profile of needs (Support Star), quality of life (EQ5D/CHU-9D), wellbeing (WEMWBS/CORS) and financial strain. We undertook 22 qualitative observations of family/link worker interactions and 39 in-depth interviews with families, link workers and healthcare professionals. Together these data were analysed within a SROI to establish the costs and social value generated. Results Of 48 families supported by the service, 25 were recruited to the evaluation (26 children, aged 10 m-15y; 4 siblings; 36 parents). Baseline quality of life and wellbeing indices averaged below population norms. Link workers were highly effective at supporting families (only 6/151 goals unmet). Unmet need decreased by 6 months (Support Star, p < 0.001). Families reported having felt overwhelmed when trying to adjust to new ways of life post diagnosis/discharge before link worker intervention, with little support to navigate non-medical needs. Parents, link workers and health care professionals found link worker support invaluable for making community services accessible. Families then felt more connected to their communities, and less isolated, with increased belief in their self-efficacy. Families and healthcare professionals felt that the duration of support, and eligibility criteria, should be extended. Inputs to deliver the service for 1 year (49 families) were estimated at £74,736: outcomes for the 18 families studied were estimated at a value of £205,861. Conclusion Hospital in-reach social prescribing is feasible, acceptable, and addresses a range of otherwise unmet needs of children with neurodisability and their families, showing a positive SROI. Other vulnerable patient groups could also benefit from this approach. Trial registration ISRCTN23306751 (2.8.22).